Thermal and Hydrochloric Acid‐Treated Montmorillonite Clay/TiO2 Nanoparticles as Potential Degrading Agent for PAHs in Solution: Adsorbent Characterization - Lekan Taofeek Popoola; Moses Oshiomah Osibuamhe; Usman Taura; Yuli Panca Asmara; Paul C. Okonkwo; Saheed Olalekan Alawode (Engineering Reports)
ABSTRACT The wide industrial purpose of polycyclic aromatic hydrocarbons (PAHs) in the production of finished products is a major factor that influences their presence in industrial wastewater discharged into water bodies. Thus, the synthesis of materials that have the potential to remove these toxic chemicals from the solution is imperative. In this study, the characterization of thermally treated and hydrochloric acid‐modified montmorillonite nanoparticles (TAMC) supported with TiO2 as a potential degrading agent for PAHs in solution was conducted using scanning electron microscope (SEM), energy‐dispersive spectroscopy (EDX), Fourier‐transform infrared (FTIR) spectrophotometer, x‐ray fluorescence (XRF), thermogravimetric analysis (TGA), powder x‐ray diffractometer (XRD), and Brunauer–Emmett–Teller (BET) method. SEM reveals the transition of montmorillonite clay (MC) from microscale to nanoscale and the formation of larger pore openings after treatment and TiO2 impregnation. FTIR reveals the presence of –OH, –C–H, Al–Mg–OH, Al–Al–OH, Al–O–Si, and Si–O–Si on the adsorbents' surface. After the thermal treatment and HCl modification, the wt% of Na+, Mg2+, Al3+, K+, Ca2+, and Fe3+ oxides in the MC reduced from 0.07, 5.2, 25.1, 1.68, 1.81, and 9.38 wt% to 0.01, 1.23, 13.96, 0.65, 0.09, and 4.38 wt%, respectively, as shown by XRF. The total pore volume, surface area, and average pore diameter increased from 0.058 cm3 g−1, 42.06 m2 g−1, and 1.129 nm to 0.164 cm3 g−1, 139.75 m2 g−1, and 4.333 nm, respectively, as revealed by BET analysis. The impregnation of TiO2 unto TAMC increased the textural properties. Adsorbents exhibit relatively similar TGA profiles but different weight loss at the examined temperature ranges. XRD reveals the presence of montmorillonite, kaolinite, feldspars, and calcite at different phase angles in all the adsorbents. The exhibited properties of the prepared thermally treated and hydrochloric acid‐modified montmorillonite nanoparticles supported with TiO2 proved it as a potential adsorbent for PAHs degradation in solution.